Oral antiretroviral pre-exposure prophylaxis reduces the risk of HIV acquisition among men who have sex with men. Issue 5 (10th May 2011) - Boily, Marie-Claude; Mâsse, Benoît R; Dimitrov, Dobromir
Abstract : Commentary on: Grant RM Lama JR Anderson PL ; iPrEx Study Team . Preexposure chemoprophylaxis for HIV prevention in men who have sex with men . N Engl J Med 2010 ;363 :2587 –99 .